2000
DOI: 10.1074/jbc.m003633200
|View full text |Cite
|
Sign up to set email alerts
|

Leucine Limitation Induces Autophagy and Activation of Lysosome-dependent Proteolysis in C2C12 Myotubes through a Mammalian Target of Rapamycin-independent Signaling Pathway

Abstract: Loss of muscle mass usually characterizes different pathologies (sepsis, cancer, trauma) and also occurs during normal aging. One reason for muscle wasting relates to a decrease in food intake. This study addressed the role of leucine as a regulator of protein breakdown in mouse C2C12 myotubes and aimed to determine which cellular responses regulate the process. Determination of the rate of protein breakdown indicated that leucine is one key regulator of this process in myotubes because starvation for this ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(141 citation statements)
references
References 45 publications
5
134
0
2
Order By: Relevance
“…In accordance with these observations, leucine infusion decreases protein degradation in human subjects (Nair et al 1992). Moreover, in mouse C2C12 myotubes, leucine starvation accounts for 30-40 % of the maximal acceleration of protein breakdown obtained with total amino acids withdrawal (Mordier et al 2000). These authors also indicated that leucine starvation induces autophagy and as a consequence an increase in lysosomaldependent proteolysis.…”
Section: Regulation Of Muscle Protein Degradationsupporting
confidence: 71%
“…In accordance with these observations, leucine infusion decreases protein degradation in human subjects (Nair et al 1992). Moreover, in mouse C2C12 myotubes, leucine starvation accounts for 30-40 % of the maximal acceleration of protein breakdown obtained with total amino acids withdrawal (Mordier et al 2000). These authors also indicated that leucine starvation induces autophagy and as a consequence an increase in lysosomaldependent proteolysis.…”
Section: Regulation Of Muscle Protein Degradationsupporting
confidence: 71%
“…31 Indeed, induction of autophagy may increase the rate of protein catabolism. 60 Whether muscle wasting in septic patients is associated with elevation of autophagy requires further investigation.…”
Section: Skeletal Musclementioning
confidence: 99%
“…Combaret et al ( 16 ) showed that dietary leucine suppresses muscle protein degradation by inhibition of ubiquitin-proteasome dependent proteolysis in rats. Mordier et al ( 17 ) showed that leucine limitation induces formation of autophagy and activation of lysosomal-dependent proteolysis in C2C12 myotube through an mTOR-independent signaling path- way. Thus leucine administration may regulate the ubiquitin-proteasome system or autophagy-lysosome system.…”
Section: Discussionmentioning
confidence: 99%